Implementasi Smart Village Untuk Meningkatkan Pelayanan Dalam Pembangunan Desa Menggunakan Metode Web Engineering - Ranti Ayunda; Roberto Kaban; Siti Jamilah Br. Tarigan; Ita Margaretta Br Tarigan (Institut Teknologi dan Bisnis Indonesia, 2025)
Village development is still uneven between one hamlet and another, causing services for village development to be somewhat hampered because they still rely on each hamlet head who reports to village officials at the Tandem Hulu I Village office, which results in village services not yet being able to reach aspects of society that can be accessed via the internet. Therefore, a system was built that could help Tandem Hulu I Village regarding monitoring development, facilities and infrastructure, development locations and development proposals. The results of this research apply an information system in the form of a website using the PHP programming language and MySQL as the database. This system was built using the Codeigniter framework. The system development method used is Web Engineering.